Routledge Handbook on Political Parties in the Middle East and North Africa (Taylor & Francis, 2020)
political parties; Middle East; North Africa
English
Keywords: Children's / Teenage: general non-fiction; Political parties; Politics & government; political parties; Middle East; North Africa